2021
DOI: 10.3390/jcm10235671
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Simplified Impression Membrane Sampling Method for the Diagnosis of Microbial Keratitis

Abstract: The purpose of this study was to compare bacterial isolation rate using a corneal impression membrane (CIM) and a sharp instrument for obtaining corneal samples from patients with suspected microbial keratitis (MK). Data was retrospectively collected for all patients that had corneal samples taken for presumed MK between May 2014 and May 2020. Prior to May 2017 samples were collected by scraping the edges of the ulcer with a blade. From May 2017, samples were collected by placing a CIM (Millicell cell culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…In this study of the 419 patients recruited, only 62% (259) were culture positive. Often the poor sensitivity is attributed to low microbial yield within the collected scrape samples . Compared with the culture-positive samples, the scrape analysis results demonstrated high sensitivity and NPV (0.89 and 0.97) and low negative LR (0.12), indicating that there were few false-negative results and that the samples tested on the LFDs contained antigen (an extracellular glycoprotein) above the limit of detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study of the 419 patients recruited, only 62% (259) were culture positive. Often the poor sensitivity is attributed to low microbial yield within the collected scrape samples . Compared with the culture-positive samples, the scrape analysis results demonstrated high sensitivity and NPV (0.89 and 0.97) and low negative LR (0.12), indicating that there were few false-negative results and that the samples tested on the LFDs contained antigen (an extracellular glycoprotein) above the limit of detection.…”
Section: Discussionmentioning
confidence: 99%
“…Often the poor sensitivity is attributed to low microbial yield within the collected scrape samples. 38,39 Compared with the culturepositive samples, the scrape analysis results demonstrated high sensitivity and NPV (0.89 and 0.97) and low negative LR (0.12), indicating that there were few false-negative results and that the samples tested on the LFDs contained antigen (an extracellular glycoprotein 31 ) above the limit of detection. While not included within the formal AspLFD analysis, 5 of the 76 culturenegative, fungal smear-positive scrape samples also had positive AspLFD results, suggesting that these patients likely had a missed Aspergillus species infection.…”
Section: Discussionmentioning
confidence: 99%
“…In view of its significant impact on human health, healthcare systems and economy, it is therefore not surprising to observe a vast amount of literature on IK, encompassing the epidemiology, risk factors, clinical characteristics, causative organisms, management, and outcomes of the disease. Large IK studies published in the recent years are summarized in Table 2 (Lin et al, 2017 , 2019 ; Tan et al, 2017 ; Khor et al, 2018 ; Peng et al, 2018 ; Green et al, 2019 ; Tavassoli et al, 2019 ; Asbell et al, 2020 ; Khoo et al, 2020 ; Kowalski et al, 2020 ; Somerville et al, 2021 ; Ting et al, 2021d ).…”
Section: Big Data In Corneal Diseasesmentioning
confidence: 99%
“…. (Lin et al, 2017(Lin et al, , 2019Tan et al, 2017;Khor et al, 2018;Peng et al, 2018;Green et al, 2019;Tavassoli et al, 2019;Asbell et al, 2020;Khoo et al, 2020;Kowalski et al, 2020;Somerville et al, 2021;Ting et al, 2021d).…”
Section: Infectious Keratitis Databasesmentioning
confidence: 99%
“…Culturing contact lenses, cases, and solutions can be useful although studies have shown a wide range of concordance of results between corneal and contact lens case samples [23 ▪▪ ,25]. A sterile impression membrane may provide diagnostic yield similar to corneal scraping [26]. Lesions where only deeper stroma is involved may benefit from passage and culture of a suture, or corneal biopsy for histopathology and culture of the deeper layers under the biopsy [23 ▪▪ ,27].…”
Section: Diagnosticsmentioning
confidence: 99%